Unlocking Opportunities: Exploring The Future Potential Of Indonesian Higher Education For Vietnamese Students - Nguyen, Minh Tri (Yayasan Ilomata, 2025)
As globalization continues to reshape the landscape of higher education, international student mobility has become increasingly prevalent. In this context, the potential of Indonesian higher education institutions (HEIs) in accommodating Vietnamese students still needs to be explored. This research delves into the prospects of Indonesian higher education for Vietnamese students, examining factors such as academic offerings, a strong cultural affinity between the two countries, language proficiency, and institutional collaborations. Through qualitative analysis of existing policies, student experiences, and academic partnerships, this study sheds light on the untapped opportunities and challenges in fostering educational exchanges between Indonesia and Vietnam. The findings suggest that Indonesian HEIs possess significant potential to attract Vietnamese students, offering diverse academic programs, affordable tuition, and a culturally enriching environment that resonates with Vietnamese students. However, language barriers, administrative hurdles, and limited awareness hinder realizing this potential. It is of utmost importance for policymakers, academic institutions, and stakeholders to urgently implement the recommendations provided in this research, thereby enhancing the accessibility and appeal of Indonesian higher education for Vietnamese students and fostering cross-cultural understanding and educational excellence in the region.